Acetate ion augmented fluorescence sensing of Zn2+ by Salen‐based probe, AIE character, and application for picric acid detection. Issue 9 (22nd February 2021) - Das, Bhriguram; Dolai, Malay; Dhara, Anamika; Mabhai, Subhabrata; Jana, Atanu; Dey, Satyajit; Misra, Ajay
Abstract: Counter anion‐triggered metal ion detection has been rarely reported by fluorimetric method. To address this challenging issue, a fluorescent probe (H2 L ) has been synthesized from bromo‐salicylaldehyde and hydrazine hydrate, and structurally characterized by single crystal X‐ray diffraction. The probe shows very weak fluorescence itself. However, its emission intensity increases in the presence of Zn 2+ over other metal ions. Surprisingly, the emission profile of this probe in presence of Zn 2+ is augmented only when acetate anion (OAc¯) is present as counter anion, that allows for precise quantitative analysis by spectroscopic studies. The compositions and complexation among the probe, Zn 2+ ion, and OAc¯ are supported by ESI‐MS, 1 H‐NMR, and Job's plot. Based on these studies, it is confirmed that the binding ratio between probe: metal is 1:2 and the detection limit (LOD) for the Zn 2+ is 2.18 µM. The probe is capable of recognizing Zn 2+ ion in the wide range of pH∼6.5‐9.5, and it could be efficiently recycled by EDTA. Furthermore, the combinatorial molecular logic gate and memory device have been constructed from the fluorescent behavior of H2 L with Zn 2+, OAc¯, and EDTA input as based on NOT and AND gates. Interestingly, the aggregation‐induced emission (AIEE) phenomenon is also perceived with greater than 50% water content in organic water mixtures, which are then useful for the detection of picric acid often used as explosive.